Voltage-gated sodium channel Nav1.5 promotes proliferation, migration and invasion of oral squamous cell carcinoma. (29th May 2019) - Zhang, Jie; Mao, Weijia; Dai, Yongzheng; Qian, Chengwei; Dong, Yang; Chen, Zhangming; Meng, Lei; Jiang, Zhe; Huang, Ting; Hu, Jie; Luo, Panquan; Korner, Heinrich; et al.
Abstract: The protein voltage-gated sodium channel Nav1.5 is highly upregulated in various types of cancer and, in general, promotes cancer cell invasiveness and metastatic progression. A previous study found that Nav1.5 was highly expressed in poorly differentiated oral squamous cell carcinoma (OSCC). However, whether Nav1.5 enhances invasiveness and metastasis of OSCC are still unknown. In this study, we found that Nav1.5 was highly expressed in OSCC cell lines compared with normal oral keratinocyte HOK cell line by using western blot analysis. CCK-8 assay results revealed that downregulation of Nav1.5 expression by its specific siRNA reduced proliferation of OSCC HSC-3 cells. Moreover, transwell assay results showed Nav1.5 knockdown significantly inhibited migration and invasion of HSC-3 cells. Meanwhile, qRT-PCR and western blot analysis results showed that epidermal growth factor (EGF) induced Nav1.5 expression in a time- and dose-dependent manner. In addition, EGF promoted proliferation, migration and invasion of HSC-3 cells. Importantly, the Nav1.5 inhibitor tetrodotoxin significantly inhibited the proliferation of HSC-3 cells and impeded the migration and invasion of HSC-3 cells. Furthermore, it was found that siRNA-mediated knockdown of Nav1.5 also lessened the proliferation of HSC-3 cells and blocked the migration and invasion of HSC-3 cells. Taken together, these results indicate that Nav1.5 is involved in the progression of OSCC and Nav1.5 promotes the proliferation, migration and invasion of OSCC cells.